(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
this article deals with the use of fairy tales in teaching primary schoolchildren in reading lesson. In addition, it provides phases, steps for analyzing context, and characteristics of fairy tale composition as well as guidelines for utilizing fairy tales in teaching process.